Hands-on learning on renewable energy – A proposed approach for technology dissemination - Budiyanto, Cucuk; Widiastuti, Indah (AIP conference proceedings, 2018)
Indonesia suffers from depletion of fossil energy resources, a similar fate as experienced by other-previously oil producer countries. Since there is no domestic conventional energy sources were discovered, the energy situation is dire that leads to dependency on imported oil and gas. Building elementary students’ awareness of renewable energy, however, may not be as simple as offering the sophisticated knowledge to adults. This paper assesses the potential contribution of hands-on learning to the understanding of elementary school students in Indonesia on renewable energy. The analysis considers the Bloom’s aspects of learning domain namely cognitive, affective and psychomotor as the starting points. A granular view on the subject was expected to set the light on the viability of the development of approaches to renewable energy dissemination.